Implementasi Tugas Pokok Dan Fungsi Pengelolaan Keuangan Pada Bagian Umum dan Keuangan Sekretariat DPRD Kota Tanjungpinang - Azahra Ashilah; Adhe Fadli Farhan; Kustiawan Kustiawan (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2025)
This study aims to evaluate the implementation of the main tasks and functions of financial management in the General and Finance Section of the Tanjungpinang City DPRD Secretariat, with a focus on identifying obstacles and formulating strategic solutions to improve the efficiency of financial management. Using a descriptive qualitative approach, data were collected through interviews, and analysis was carried out based on Edward III's policy implementation theory which emphasizes four key variables: communication, resources, disposition, and bureaucratic structure. The results of the study indicate that the implementation of the main tasks and functions is running quite well, supported by effective internal communication, the availability of human resources, budget, and infrastructure, as well as a bureaucratic structure that still faces challenges, such as minimal technical training and vacancies in functional positions that have an impact on bureaucratic effectiveness. Capacity building and structural arrangements are needed so that financial management can run more optimally, accountably, and in accordance with the principles of good governance.